An automated system for calibration table calculation of cylindrical horizontal tanks - Proskurenko, Denis; Bezuglyi, Mykhailo (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2026)
The article presents the results of the development and implementation of the software "Automated Calculation of Calibration Table" for the calibration of steel cylindrical horizontal tanks obtained using 3D laser scanning. The proposed system automates the processing of 3D point clouds using a hybrid segmentation method (RANSAC and DBSCAN) and improved geometric formulas for calculating a per-millilitre capacity table. The results of calculating volumes and capacity coefficients are compared with alternative enterprise software, which demonstrates an increase in accuracy by 5–15% and a reduction in processing time by 70–80%. The developed software adapts to tank deformations, ensuring reliability in industrial conditions, which is confirmed by data analysis for 10 tanks with a cloud density of 5–15 million points.